Correlation of Serum CA-125 Levels with Ultrasound Doppler Indices in Ovarian Neoplasms - Sehrish Sabir, Aassia Fazal, Yamna Sabahat Chaudhry, Shazia Aman, Humna Ashraf, Azqa Zafar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Elevated serum CA-125 is widely used in the assessment of ovarian neoplasms, while Doppler ultrasonography provides dynamic vascular information potentially reflective of malignant transformation. The present case-control study aimed to evaluate the correlation between preoperative serum CA-125 levels and colour-Doppler ultrasound indices (resistance index [RI], pulsatility index [PI], peak systolic velocity [PSV]) in women with ovarian tumors and to determine their combined value in distinguishing benign from malignant lesions.